A Comparison of Two Anastomotic Techniques in the Jejunum of the Goat - H. A. Al-Timmemi; Karim Al-Jashamy; Mohammed S. Dauod (Veterinary Medicine International)
This study was carried out to test two different anastomotic techniques to identify advantages and disadvantages of each technique in goats. All animals were under local infiltration anaesthesia. A five-cm length of jejunum was resected from the first part of the jejunum and end to end anastomosis using 3-0 Polygalactin-910 with one row of sero-submoucosal interrupted sutures (SSIS) group, and one row of horizontal mattress interrupted sutures (HMIS) group. Two animals from each group were euthanized on the 4th, 14th and 21st postoperative days. A 7-cm segment of jejunum including the anastomosed area was resected from each animal. There was no significant adhesion between anastomosis area and surrounded tissues observed in SSIS animals, while there was significant adhesion between anastomosis area and surrounded tissues which were observed in HMIS animals. Stenosis degree was lower in the SSIS than the HMIS group. The bursting pressure was higher in the SSIS than the HMIS group. Macroscopic evaluation indicated that the anastomotic line mucosa was abridged better with less local edema in the SSIS group. Histological evaluation in the SSIS group showed almost all parameters such as epithelial recovery and repair of submucosal-mucosal layer demonstrated better healing compared to the HMIS group.